2019
DOI: 10.5194/acp-19-7595-2019
|View full text |Cite
|
Sign up to set email alerts
|

New particle formation events observed at the King Sejong Station, Antarctic Peninsula – Part 2: Link with the oceanic biological activities

Abstract: Marine biota is an important source of atmospheric aerosol particles in the remote marine atmosphere. However, the relationship between new particle formation and marine biota is poorly quantified. Long-term observations (from 2009 to 2016) of the physical properties of atmospheric aerosol particles measured at the Antarctic Peninsula (King Sejong Station; 62.2 • S, 58.8 • W) and satellitederived estimates of the biological characteristics were analyzed to identify the link between new particle formation and m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 88 publications
(114 reference statements)
3
36
1
Order By: Relevance
“…For instance, Weller et al (2015) reported that the GR at the Neumayer station varied between 0.4 and 1.9 nm h −1 , with an average of 0.90 ± 0.46 nm h −1 . However, our results are lower than those reported by Järvinen et al (2013), who studied NPF events at the Concordia station Dome C from December 2007 to November 2009 and showed a GR of 4.3 nm h −1 . This discrepancy is likely attributed to the number of analyzed days.…”
Section: Calculation Of Other Parameters Based On Size Distribution Datacontrasting
confidence: 98%
See 3 more Smart Citations
“…For instance, Weller et al (2015) reported that the GR at the Neumayer station varied between 0.4 and 1.9 nm h −1 , with an average of 0.90 ± 0.46 nm h −1 . However, our results are lower than those reported by Järvinen et al (2013), who studied NPF events at the Concordia station Dome C from December 2007 to November 2009 and showed a GR of 4.3 nm h −1 . This discrepancy is likely attributed to the number of analyzed days.…”
Section: Calculation Of Other Parameters Based On Size Distribution Datacontrasting
confidence: 98%
“…Approximately 72 % of the NPF occurred during the summer period, showing the highest value of 38 % in January. The clear difference in the frequency of the NPF events in austral summer and winter periods indicates that solar intensity and temperature play important roles in the formation and growth of aerosol particles, along with precursor vapors derived from marine biota activities in Antarctica (Virkkula et al, 2009;Weller et al, 2015;Jang et al, 2019). The FR of particles ranging from 2.5 to 10 nm varied from 0.16 to 9.88 cm −3 s −1 , with an average of 2.79 ± 1.05 cm −3 s −1 .…”
Section: Backward Trajectory Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary aerosol production occurs through the nucleation of gaseous precursors (e.g., sulfuric acid, ammonia, halocarbons, isoprene, and monoterpenes; Kulmala & Kerminen, ; Kirkby et al, ; Ehn et al, ; Ovadnevaite et al, ). Recently, several field and laboratory studies have shown that the physiochemical properties of primary and secondary marine organic aerosols are significantly related to biological activities at the ocean surface (O'Dowd et al, ; Facchini, Decesari, et al, ; Facchini, Rinaldi, et al, ; O'Dowd et al, ; Park et al, ; Rastelli et al, ; Jang, Park, et al, ).…”
Section: Introductionmentioning
confidence: 99%